2010
DOI: 10.1159/000322076
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes for Rhinogenic Contact Point Headaches

Abstract: Objective: To evaluate the surgical outcome in patients diagnosed as having rhinogenic contact point headaches (RCPH). Subjects and Methods: Thirty-six patients (aged 17–58 years) with RCPH underwent mini functional endoscopic sinus surgery procedures. Patients’ pain complaints were evaluated with a visual analog scale (VAS) both pre- and postoperatively. Results: All patients reported a decrease in the intensity of pain postoperatively. Nineteen patients (52.7%) reported complete relief. The difference betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…Nasal mucosal contact points may contribute to airflow resistance and these contact points are more prevalent in brachycephalic dogs (Schuenemann & Oechtering ,). In humans, nasal mucosal contact points are frequently associated with nasal blockage and reduction in olfactory sensation and they may additionally be associated with contact‐point headaches (Bieger‐Farhan et al , Behin et al , Bektas et al , Moche & Palmer , Harrison & Jones , Roozbahany & Nasri , Sadeghi et al , Kim ). Multiple anatomical variations of nasal contact points exist in humans and in order to establish a proper therapeutic plan, an individualised thorough assessment combining clinical history, patient examination, computed tomography (CT) imaging and endoscopy is ideal (Roozbahany & Nasri ).…”
Section: Introductionmentioning
confidence: 99%
“…Nasal mucosal contact points may contribute to airflow resistance and these contact points are more prevalent in brachycephalic dogs (Schuenemann & Oechtering ,). In humans, nasal mucosal contact points are frequently associated with nasal blockage and reduction in olfactory sensation and they may additionally be associated with contact‐point headaches (Bieger‐Farhan et al , Behin et al , Bektas et al , Moche & Palmer , Harrison & Jones , Roozbahany & Nasri , Sadeghi et al , Kim ). Multiple anatomical variations of nasal contact points exist in humans and in order to establish a proper therapeutic plan, an individualised thorough assessment combining clinical history, patient examination, computed tomography (CT) imaging and endoscopy is ideal (Roozbahany & Nasri ).…”
Section: Introductionmentioning
confidence: 99%
“…So in our study we have 17 (85%) patients responded to surgery but only 3 patients with poor response (15%). The post-operative improvement was statistically highly significant as the p value was 0.003 calculated by binomial method [4][5][6][7]. In our study all those with complete response to xylocaine test had complete relieve of headache, and those with no improvement in their headache had partial response to xylocaine test, indicating that the xylocaine test is good prognostic indicator.…”
Section: Resultsmentioning
confidence: 56%
“…In 1997, Clerico et al [31] have reported results from 19 patients treated surgically for refractory primary headaches during a mean follow-up period of 21 months and the success rate was 79%. However, success rates of almost 90% have been reported for shorter follow-up periods of about 13 months [1,32,39], while after a follow-up period of 2 years, Welge-Luessen et al [34] showed an 85% success rate among their patients of which 60% were completely free of pain and 25% experienced a significant improvement. This rate decreased to 65%, with only six patients being free of symptoms after 10 years.…”
Section: Discussionmentioning
confidence: 99%